Provenance Analysis and Diagenetic Control of Early Cambrian Kussak Formation, Upper Indus Basin, Pakistan - Pervaiz, R.; Umar, M.; Wajid, A.A.; Khan, J.K.; Israr, A.; Rehman, S.U.; Pervaiz, A. (The Nucleus, 2017)
Petrographic study of sedimentary rocks can be used to determine provenance and diagenetic histories. Thirty samples from Kussak Formation were collected from Khewra Gorge, Eastern Salt Range, Pakistan, for petrographic studies. Petrographic analysis revealed that Kussak Formation consists of quartz with mean value of 85.2%, while feldspar accounts for no more than 3% of total grains. Lithic fragments and a variety of heavy minerals were observed in traces and cumulatively amounts to 2.5%. Silica, calcite, and iron oxide, as cementing materials, were also detected in sandstone and contribute 4% overall. The amount of Monocrystalline quartz is computed to be more abundant than polycrystalline quartz. Based on McBride classification, sandstone of Kussak Formation is classified as quartz arenite. Higher quartz content most likely places the source of Kussak Formation in the Indian Shield. Compaction, iron oxide cementation, calcite cementation, replacement, dissolution, precipitation of silica as overgrowth and alteration of framework grains are the prominent diagenetic modifications, which were observed and analyzed in Kussak Formation. Deep burial, high pressure and temperature regime, as evident from quartz overgrowths and grain fracturing, point towards final phase of diagenesis for Kussak Formation.